Purification, Partial Characterization, and Evaluation of the Antiulcer Activity of Calotropis procera Leaf Lectin - Al-Thobaiti, Saed A.; Konozy, Emadeldin Hassan E. (Protein and Peptide Letters, 2022)
Background: Lectins are proteins with therapeutic and diagnostic potential that can be applied in battling various ailments. Aim and Objective: This study was designed to purify and characterize the hemagglutinating activity derived from the leaves of Calotropis procera and its possible role in protecting the stomach against ethanol-induced lesions. Methods: The Calotropis procera leaf lectin (ProLec), was isolated by homogenization of the defatted leaf powder in Phosphate-Buffered Saline (PBS) and purified by affinity chromatography on Sephadex G-100. The lectin was eluted from the affinity column by 3% acetic acid and was physicochemically characterized. In a dose-dependent manner, ProLec was administered to rats with ethanol-induced ulcers, and biochemical, histopathological, and toxicological examinations were performed. Results: ProLec is a heterodimer of 75 and 68 kDa. It agglutinated all human RBCs, whereas it showed weak interaction with animal erythrocytes. The protein was optimally active at 25 °C and was labile above this temperature. ProLec exhibited two pH optima and was a metalloprotein requiring Ca, Mn, and Ni. It contains 1.6% tryptophan residues of which about 1% is exposed and critical for lectin activity. The lectin exhibited a potent gastroprotective effect against ethanolinduced gastric lesions with no apparent toxicity to both kidneys and liver. Examination of the pH of the gastric juice of lectin-treated animals indicated a possible role of lectin in maintaining stomach acidity within the normal ranges compared to the gastric juice pH of animals that received ethanol only. Conclusion: These results may suggest that ProLec could conceivably be a good future drug for the treatment of gastric ulcers, however, extensive immunological and toxicological research remains to be done.
Keywords: purification